The Effect of Special Physical And Skill Exercises For Developing Lower Extremities EMG and Its Relationship With the Accuracy Of Spiking In Volleyball - Sabah, Omer (Journal of Physical Education, 2018)
The Effect of Special Physical And Skill Exercises For Developing Lower Extremities EMG and Its Relationship With the Accuracy Of Spiking In Volleyball The purpose of this study is to investigate the effect of special exercises on EMG of the lower limb muscles on the one hand and the relationship between the EMG of the lower limb muscles and spiking accuracy. The research hypothesized statistical differences between pre and posttest and the correlation between the EMG of the lower limb muscles and spiking accuracy in the variables understudy. The researcher used the experimental method. The subjects were (10) players from the National Center for gifted in volleyball players aged (17-19) years. The pre tests were conducted followed by the application of special exercises that consisted of (24) training sessions and (18) physical session and (6) skill sessions distributed over (8) weeks with (3) units per week. The data was collected and treated using proper statistical operations to come up with the conclusion and recommendations.